Macromol. Chem. Phys. 18/2017. Issue 18 (September 2017) - Kimura, Yoshihiko; Terashima, Takaya; Sawamoto, Mitsuo
Abstract : Frontispiece : Amphiphilic random copolyacrylamides bearing hydrophilic poly(ethylene glycol) and hydrophobic dodecyl pendants induced controlled self‐assembly in water to provide size‐controlled uni‐core micelles and necklace (multi‐core) micelles. This is reported by Yoshihiko Kimura, Takaya Terashima, * and Mitsuo Sawamoto* in article number1700230 .